Unilateral Cerebellar and Brain Stem Hypoplasia in a Child with a Postnatal Diagnosis of Dissecting Aneurysm in Basilar Artery - Akkas-Yazici, Sinem; Benbir, Gulcin; Kocer, Naci; Yalcinkaya, Cengiz (Neuropediatrics, 2014)
Cerebellum is highly vulnerable in the prenatal period. Increasing experience with fetal imaging studies has demonstrated that unilateral cerebellar hypoplasia (UCH) is mainly prenatally acquired, representing disruption rather than a true malformation. Here, we report the case of a 17-month-old boy presented with a sudden onset of abnormal eye movements, who was diagnosed during routine fetal screening with UCH and brain stem hypoplasia and suffered from cerebral palsy; however, no posterior arterial system pathology was detected on cranial magnetic resonance images at that time. Following this acute event, diagnostic neuroradiological interventions revealed a dissecting aneurysm with a saccular component in midbasilar arterial segment and hypoplastic left posterior cerebral artery, which may support the ischemic disruptive mechanism in the development of prenatally detected UCH in this child. The pathogenetic mechanisms for cerebellar disruption are certainly multifactorial in origin, although ischemic arterial etiologies were often undervalued.
Keywords: unilateral cerebellar hypoplasia; cerebellar disruption; prenatal disruptive etiologies; ischemic stroke in early childhood; childhood aneurysms of posterior cerebral circulation